Water diffusivity in PA66: Experimental characterization and modeling based on free volume theory. (June 2015) - Broudin, M.; Le Gac, P.Y.; Le Saux, V.; Champy, C.; Robert, G.; Charrier, P.; Marco, Y.
Graphical abstract: Highlights: The paper presents original water absorption results for polyamide 6.6. An important influence of water activity on water diffusion kinetic is observed when amorphous phase is in rubbery state. The influence of water activity on diffusivity can be predicted based on physical consideration, i.e. the free volume theory. Abstract: Diffusion of water in polyamide 6.6 has been characterized for a wide range of temperatures (from 25 to 80 °C) and various humidities using dynamic vapor sorption machine. The decrease in glass transition temperature ( Tg ) has also been measured using DMA tests. As usually observed, PA66 absorbs a large amount of water (up to 5% at 90%RH) with a Fickian behavior with a diffusion coefficient that depends on water activity for all temperatures. Moreover, it appears that the diffusion coefficient for tests performed below Tg is almost independent of the water activity whereas a strong dependency is observed above Tg . This behavior is to be compared to a large decrease of Tg with the absorption of water. The increase of the water diffusion can therefore be related to a change of the amorphous phase (the crystalline phase is supposed to absorb no water) from the glassy to the rubbery states. A model based on the free volume theory is used successfully to describe the wide experimental database. It is therefore possible to describe the dependency of the water diffusion kinetics on both temperature and water uptake using the approach described in this paper.